Influence of process parameters on single bed Ni/(Al)MCM-41 for the production of propene from ethene feedstock. (31st December 2019) - Felischak, Matthias; Wolff, Tanya; Alvarado Perea, Leo; Seidel-Morgenstern, Andreas; Hamel, Christof
Graphical abstract: Highlights: Direct production of propene from ethene feedstock using Ni/(Al)MCM-41. Reaction network analysis indicates the occurrence of cracking reaction. Cyclic reactor operation is suggested, including deactivation and regeneration. A single catalyst bed was applied for more than 2000 h on stream. Abstract: A Ni aluminized mesoporous MCM-41 catalyst was prepared and applied for the direct conversion of ethene to propene. Suitable ethene conversion and good selectivity for the desired molecule propene were achieved. The catalyst placed in a packed tubular reactor was stable for more than 2000 h with time on stream. A reaction network analysis was performed evaluating the product spectrum observed covering a large range of operating conditions. Thereby, temperature and feed concentration can be considered as significant influence parameters on the product distribution. Based on the product spectra, a modified reaction network including a catalytic cycle is suggested, which adds cracking of long-chain olefins to the conventionally considered dimerization/oligomerization and isomerization steps. Following previous publications, the catalyst presented strong deactivation behavior. It was observed that the regeneration conditions (oxygen concentration and regeneration time) are crucial parameters concerning long-time stability. Finally, a cycling reactor operation of deactivation-regeneration steps is suggested.